Biyaheng Marikina a narrative documentary on Marikina City - Mendita, Heide Anne F.; Nazario, Mona Liza T.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This thesis is a narrative documentary about the City of Marikina. It is comprised of a written report and a video production that shows Marikina's history, local government, environment, industry, different sights, culture and the Marikeños way of life. The researchers decided to make a production thesis because they believe that a thesis as such is a culmination of all the things they've learned in their Broadcast Communication course. They chose to make a narrative documentary of Marikina City because it is a new developing city, which they believe needsa the proper promotion and exposure to the Filipino people. The researchers/producers conducted a survey which showed that the target audience, college students from Metro Manila, would like a documentary to be presented in a lively, informative, and upbeat style fit for their generation. In line with their production thesis the researchers took footages of Marikina and conducted various interviews, which included the City Mayor Bayani Fernando. Through the process of their research and production, the researchers found out that the City of Marikina is well awarded for all their major programs. These include the Marikina River Park and Development and the Squatter-Free Marikina, which are both winners of the Galing Pook Award. Marikina has also been praised and awarded for their undertaking on the Hassle Free Roadways, Effective Waste Management Through Deployment of Proper Engineering (Garbage Transfer Station), Puno Kahit Saan, Emergency Rescue 161, Development of the People's Mall (Mall ng Bayan), Barangay Talyer, Sports for Health and Wealth, Disiplina sa Bangketa, Bantay Bayan and many more. Using the footage and data that the researchers/producers had gathered they produced a narrative documentary. It combined a story woven by the actors that helped narrate the accounts of the Documentary of Marikina. This thesis gives a descriptive account of the researcher/producers findings through the course of their data gathering and production.
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Marikeños way of life -- Philippines